A Global Meta-analysis of the Prevalence of HIV, Hepatitis C Virus, and Hepatitis B Virus Among People Who Inject Drugs—Do Gender-Based Differences Vary by Country-Level Indicators?. (6th February 2019) - Leung, Janni; Peacock, Amy; Colledge, Samantha; Grebely, Jason; Cunningham, Evan B; Hickman, Matthew; Vickerman, Peter; Stone, Jack; Trickey, Adam; Dumchev, Kostyantyn; Lynskey, Michael; Hines, Lindsey; et al.
Abstract: Background: Women-specific factors exist that increases vulnerability to drug-related harms from injection drug use, including blood-borne viruses (BBVs), but gender-based differences in BBV prevalence have not been systematically examined. Methods: We conducted meta-analyses to estimate country, regional, and global prevalence of serologically confirmed human immunodeficiency virus (HIV), hepatitis C virus (HCV; based on detection of anti-HCV antibody), and hepatitis B virus (HBV; based on detection of HBV surface antigen) in people who inject drugs (PWID), by gender. Gender-based differences in the BBV prevalence (calculated as the risk among women relative to the risk among men) were regressed on country-level prevalence and inequality measures (Gender inequality index, Human development index, Gini coefficient, and high, low or middle income of the country). Results: Gender-based differences varied by countries and regions. HIV prevalence was higher among women than men in sub-Saharan Africa (relative risk [RR], 2.8; 95% confidence interval [CI], 1.8–4.4) and South Asia (RR, 1.7; 95% CI, 1.1–2.7); anti-HCV was lower among women in the Middle East and North Africa (RR, 0.6; 95% CI, .5–.7) and East and Southeast Asia (RR, 0.8; 95% CI, .7–.9). Gender-based differences varied with country-levels of the BBV prevalence in the general population, human development, and income distribution. Conclusion: HIV was more prevalent in women who inject drugs as compared to their male counterparts in some countries, but there is variation between and within regions. In countries where women are at higher risks, there is a need to develop gender-sensitive harm-reduction services for the particularly marginalized population of women who inject drugs. Abstract : Relative to men, women had a higher human immunodeficiency virus prevalence in sub-Saharan Africa and South Asia and a lower anti–hepatitis C virus antibody prevalence in Middle East and North Africa and East and Southeast Asia, compared with men. Gender-based differences varied with country levels of human development and income distribution.